Transformation of public library websites in Indonesia - Nove Eka Varian Anna, NOVE (Emerald Insight, 2018)
Purpose This paper aims to observe the province’s public library websites in Indonesia and to give some recommendation about knowledge portal website that can support the creation and invention of knowledge. Design/methodology/approach Data and information were gathered by observing library websites at the provincial level to see the digital survey and collection. This survey includes 34 province public library websites in the period from August 1 to 15, 2017. As the survey focuses on the availability of online digital collections, availability of digital services such as the user can have conversation with the librarian through a chat reference service, the availability of trusted external information sources, the availability of user forums for discussion. Findings The result of the research showed that the public library websites in Indonesia are still static (less interactive) and only give standard information about the library services, its operational hours, contact numbers and their collection. According to the result, it is recommended for every public library transforms its website into a knowledge portal website that can give a real and direct effect to the users, especially in the creation of innovation. Originality/value This paper also recommends a framework for a knowledge portal that includes e-resources, user needs, partnership, internet resources, integrated OPAC and collaboration. A survey on a library website is rarely conducted in Indonesia; therefore, this result will be beneficial for developing library websites.